2011
DOI: 10.1007/s10546-011-9663-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Australian Urban Climate in a Mesoscale Atmospheric Numerical Model

Abstract: We develop an urban canopy scheme coupled to a mesoscale atmospheric numerical model and evaluate the simulated climate of an Australian city. The urban canopy scheme is based on the Town Energy Budget approach, but is modified to efficiently represent the predominately suburban component of Australian cities in regional climate simulations. Energy conservation is improved by adding a simple model of air-conditioning to prevent the urban parametrization acting as an energy sink during the Australian summer. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…The rising temperature in response to the growth of both cities can be captured by the explanation that, as population grows, urbanization increases and the magnitude of the urban heat island also expands [58]. Similar findings were obtained in Australia between 1951 and 2003, where land cover changes produced statistically significant warming [59].…”
Section: Discussionsupporting
confidence: 60%
“…The rising temperature in response to the growth of both cities can be captured by the explanation that, as population grows, urbanization increases and the magnitude of the urban heat island also expands [58]. Similar findings were obtained in Australia between 1951 and 2003, where land cover changes produced statistically significant warming [59].…”
Section: Discussionsupporting
confidence: 60%
“…The urban canopy model developed by Ryu et al (2011) considered the impacts of urban surface water (the maximum water depth on roofs and roads was set to 1 mm). Thatcher et al (2012) introduced a simplified big-leaf model in the urban canopy model to determine the impacts of vegetation in urban street canyons. Kotthaus et al (2012) analyzed the contributions of anthropogenic sources to sensible and latent heat flux at building scales by observing the urban SEB.…”
mentioning
confidence: 99%
“…In addition, effects of aerosols on the radiation and on the cloud microphysics are considered (Rotstayn and Lohmann, 2002;Rotstayn et al, 2011), which are shown to be important for the simulations of severe convective storms (Lompar et al, 2017). In order to account for processes within the urban canopy layer, CCAM employs a state-of-the-art urban parameterization based on the Town Energy Budget (TEB; Masson, 2000), approach denoted here as aTEB (Thatcher and Hurley, 2012;Luhar et al, 2014;Lipson et al, 2017), which is coupled to the Community Atmosphere Biosphere Land Exchange model (CABLE) land-surface scheme (Kowalczyk et al, 2013). Compared to the original approach by Masson (2000) aTEB has an improved representation of suburban areas, an in-canyon vegetation parameterization, an additional parameterization for air-conditioning and an improved thermal conduction model.…”
Section: Forecast Modelmentioning
confidence: 99%